Comparison of selected performance-associated parameters after off-season and two-month training preparation in professional Czech ice hockey players - Neuls, F.; Botek, M.; Krejcí, J.; Sigmund, M. (Acta Gymnica, 2023)
Background: In ice hockey, regular off-ice testing can serve as a controlling mechanism for a training program's effectiveness.